Anti-TGF-β strategies for the treatment of chronic liver disease - Breitkopf-Heinlein, Katja; Haas, Stephan; Wiercinska, Eliza; Singer, Manfred V.; Dooley, Steven (Alcoholism, 2005)
Abstract: Permanent alcohol abuse may lead to chronic liver injury with deleterious sequelae such as liver cirrhosis and hepatocellular carcinoma. Mechanisms of fibrogenesis encompass recruitment of inflammatory cells at the site of injury and cytokine mediated activation of hepatic stellate cells (HSC) with accumulation of interstitial collagens. HSC transdifferentiation and accompanying apoptosis result in destruction of liver architecture and are therefore key steps of disease progression. TGF-β represents the main profibrogenic cytokine in liver fibrosis and other fibroproliferative disorders by inducing extracellular matrix deposition as part of the wound healing response. In parallel, TGF-β triggers hepatocytes that are strongly responsive for this cytokine, to undergo apoptosis, thereby providing space for HSC proliferation and generation of a collagenous matrix. Anti TGF-β approaches were established and successfully utilized for the treatment of experimental fibrogenesis. Dominant negative TGF-β receptors (TβR), generated by fusing the Fc domain of human IgG and the N-terminal (extracellular) fragment of TβRII (Fc:TβRII) were applied to suppress fibrosis. Similarly TGF-β binding proteins like decorin, antagonistic cytokines such as bone morphogenetic protein-7, hepatocyte growth factor, IL-10, or IFN-γ were as efficient as camostat mesilate, a protease inhibitor that possibly abrogated proteolytic activation of TGF-β. Further, our group recently overexpressed Smad7 in bile duct ligation induced liver fibrosis and achieved efficient inhibition of intracellular TGF-β signaling, thereby counteracting profibrogenic effects in cultured HSC and in vivo. A direct link between the effect of alcohol and TGF-β exists through reactive oxygen species that are generated in liver cells by alcohol metabolism and represent activators of TGF-β signaling. Thus, soluble TβRII expression reduced experimental fibrogenesis in vitro and in vivo partially by decreasing intracellular ROS and inhibiting NADH oxidase. Approaches that specifically target profibrogenic TGF-β signaling are promising to treat alcoholic liver disease in the future. However, to ensure safety for the patients to be treated, approaches with strong specificity need to be established. Therefore, it is essential to delineate the profibrogenic actions of TGF-β and the influence of alcohol abuse in molecular detail.